Selective microbial resolution of lupanine racemate: Bioprocess development and the impact of carbon catabolite repression on industrial wastewater valorisation - Parmaki, Stella; Esteves, Teresa; Gonçalves, João M J; Catenacci, Arianna; Malpei, Franscesca; Ferreira, Frederico C.; Afonso, Carlos A.M.; Koutinas, Michalis (My University, 2022)
An environmentally friendly bioprocess for the valorisation of the lupanine enantiomeric mixture existing in lupin bean processing wastewater was developed. Pseudomonas putida LPK411, which is capable of enantioselectively biodegrading lupanine enantiomers, was employed for the resolution of the lupanine racemate content of unrefined and pretreated industrial effluents. The optimal culture conditions for racemic lupanine biodegradation by LPK411 were determined as 31 °C, pH 6–7, and 1.5 g L−1 initial lupanine concentration. The results obtained for enantioselective resolution of the effluents by P. putida LPK411, grown in shake-flasks, and a lab-scale bioreactor under batch operation, demonstrated that lupanine resolution was substantially improved in the bioreactor, exhibiting L-(–)-lupanine enantiomeric excess > 93% for all feedstocks used. Moreover, a fed-batch bioprocess was conducted using racemic lupanine resulting in 53% and 49% enhanced D-(+)-lupanine biodegradation and biomass production compared to the corresponding batch experiment respectively, while L-(–)-lupanine concentration increased by 49%. Monitoring the transcriptional kinetics of luh and crc genes employing industrial wastewater and the alkaloid racemate in synthetic media demonstrated that although expression from the lupanine catabolic route was rapidly induced upon supply of lupanine as a single substrate, LPK411 preferably utilised other carbon molecules of the real effluent over lupanine, suppressing the alkaloid’s catabolic pathway via the carbon catabolite repression regulatory system. The study exemplified the impact of a preferred compound on the main metabolic route of a bioprocess, demonstrating the importance of molecular interactions in biorefineries developed based on the mixture of substrates contained in renewable bioresources. Future research should aim at optimising and up-scaling the enantioselective biodegradation process proposed.
Keywords: Lupanine; Chiral resolution; Fed-batch; Enantiomeric excess; Pseudomonas putida LPK411; Gene expression